Homo (not really) sapiens - Piechowicz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
For millennia, philosophers have pondered the question, “Who are we?” It becomes a burning question at an age of scientific and technological civilization and a world full of conveniences, mainly because human life is still not comfortable. Adam Hart takes up the challenge of confronting the evolutionary achievements of the Homo species and the environment it has produced, showing that our life—for fundamental reasons—cannot be the realization of idyllic visions.
Keywords: philosophy; evolution; culture; contemporary world